Identity Processing Style and Depression: The Mediational Role of Experiential Avoidance and Self-Regulation. Issue 2 (3rd April 2019) - Berzonsky, Michael D.; Kinney, Andrew
ABSTRACT: This study investigated the role experiential avoidance and self-regulation play in mediating relationships between stylistic differences in the way college students engage or attempt to evade the process of constructing a personal sense of identity and depressive symptoms. Two hundred seven 18- to 23-year-old undergraduate students completed measures of identity processing style, self-regulation, experiential avoidance, and depressive symptoms. Consistent with previous research, a diffuse-avoidant identity style was positively associated with depression, which was completely mediated by self-regulation and experiential avoidance. Contrary to prediction, an informational identity style was not directly related with experiential avoidance or depression. However, an informational style indirectly predicted low depressive symptoms via self-regulation. Unexpectedly, when the contribution of self-regulation was controlled, an informational style was positively associated with experiential avoidance, which indirectly predicted high depressive symptoms. The pattern of relationships was not moderated by the sex of the participants. Implications of the results for intervention programs and counseling practices that may enhance the mental health of college students are considered.